Evaluación a nivel de laboratorio de las características químicas y mecánicas del comportamiento de un material compuesto a partir de matrices de resina epoxi mezcladas con ripio de llanta en diferentes proporciones para su utilización como material alternativo en diversos campos de la industria. (2022)
In this project, destructive tests were carried out in order to find the chemical and mechanical characteristics of a composite material based on epoxy resin and tire debris in different proportions. The tests carried out consisted of tension and bending tests for the mechanical characteristics, and morphological analysis and solubility tests in different solvents, which were; benzene, caustic soda and sulfuric acid, for the chemical characteristics, in order to find the most favorable application as an alternative material in the broad context of the industry.